THE INFLUENCE OF MANAGER’S ENTREPRENEURIAL ATTITUDE AND MANAGER’S ENTREPRENEURIAL COMPETENCE ON ORGANIZATIONAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES (SMES) - Dewi, Liliana; Christian, Sonata (Jurnal Entrepreneur dan Entrepreneurship, 2017)
This study aims to test the influence of manager’s entrepreneurial attitude and manager’s entrepreneurial competence on organizational performance of Small and Medium Enterprises (SMEs). SMEs are highlighted for their fame in creating jobs in the society and for their ability in increasing the rate of economic growth and in ensuring economic stability. However, there are some doubts on the influence of Manager’s Entrepreneurial Attitude and Manager’s Entrepreneurial Competence on Organizational Performance, which the study attempts to clarify. In this study, questionnaires were distributed to the managers of SMEs or their representatives, or other parties that understand the operation and the management of those SMEs. The sample size consisted of 35 respondents, and the acquired data were analyzed using multiple regression analysis. The result showed that manager’s entrepreneurial attitude affects organizational performance, while manager’s entrepreneurial competence does not.